Prevalence of dental caries among government primary school children: a cross-sectional study - Kumar A. R., Harish; B. B., Bhavani (International Journal Of Community Medicine And Public Health, 2022)
Background: Oral health is fraction of the whole health portion. The causal link connecting oral and complete disease has been revealed in recent years. Oral wellbeing has also affected the quality of life deeply. The extremely prevalent diseases in many communities include dental cavities and parodontal diseases. Once they happen, and even with complex etiology, they are rather irreversible. While there are primary preventive strategies, they do not offer maximum security. Methods: A total of 200 school children were selected randomly and dental caries assessment was recorded according to DMFT/DMFS indices. Results: Dental Caries was found to be 76 (38.0%) with mean DMFT scores 2.22±2.404 and mean DMFS scores 5.46±7.242, gender wise DMFT scores of school children is 2.22±2.404 and DMFS scores of school children is 5.46±7.242. The highest prevalence of dental caries 48.8% (mean dmft 2.27) was seen in 10-year children, followed 45.7% (mean dmft 1.69) was seen in 6-year children, 37.0% (mean dmft 2.3) was seen in 8-year children, 31.4% (mean dmft 2.26) was seen in 9-year children and lowest prevalence of dental caries 27.9% (mean dmft 2.49) was seen in 7-year children and females with 42.7% (mean dmft 2.15) and males with 32.2% (mean dmft 2.15). Conclusions: There is an urgent need to change from restorative dental services to preventive oriented dental services for government primary school children to improve the oral health status.